Determinação da espessura óssea entre o centro do forame apical e as superfícies externas das corticais na dentição permanente humana em imagens de tomografia computadorizada de feixe cônico - Porto, Olavo Cesar Lyra (2018)
The aim of this study was to determine the thickness of the root apex in relation to cortical buccal and lingual / palatal human permanent teeth using computed tomography cone beam images (CBCT). A sample of 1,400 CBCT examination teeth from 422 patients (394 women, mean age of 44.46) was selected. The determination of the thickness of the apical foramen with the vestibular and lingual / palatal cortical was determined in CBCT images in the axial, coronal and sagittal sections, with reference to the center of the apical foramen and the external portion of the buccal and lingual / palatal cortical. The mean and standard deviation of the quantitative variables were obtained. The normality of the data was evaluated by the Kolmogorov-Smirnov test. Analysis of the comparison of independent samples was assessed by the t-Test for independent samples or by the Mann-Whitney Test. Values of p <0.05 were considered significant. The results showed that in the upper and lower anterior teeth the smaller bone thicknesses are directed towards the vestibular cortical. The lowest cortical vestibular thickness was found in the superior canine (1.49mm ± 0.86) followed by the upper central incisor (1.59mm ± 0.67). The greater cortical lingual / palatal thickness was found in the superior canine (8.63 ± 2.08) followed by the upper central incisor (7.07 ± 1.96). The lowest thickness was found in the cortex of the buccal root of the first (1.13 ± 0.68) and second (2.20 ± 1.21) premolars. The greatest cortical thickness lingual / palatal was found in the palatal cortex of the first (8.07 ± 1.63) followed by the second (7.62 ± 1.84) upper premolars. In the first upper molar the smallest thickness was found in the buccal cortical of the mesiobuccal root (1.98 ± 1.33). In the second lower molar, it was verified that the buccal cortical (8.36 ± 1.84) was thicker than the lingual cortical (2.95 ± 1.16). Knowledge of the anatomy of different dental groups and adjacent structures such as bone thickness of alveolar cortices influences the quality of surgical therapeutic planning, as well as guides the analysis of bacterial dissemination pathways in periapical infections. The CBCT allows to obtain linear measures that favor comparative analysis.